Kajian Efektivitas Metode Branch and Bound dan Metode Cutting Plane dalam Optimasi Jumlah Produksi di BSL Store - Tri Rahmayani; Devni Prima Sari (UNIVERSITAS NEGERI PADANG, 2022)
BSL Store is one of the Small and Medium Enterprises (SME) in Tangerang Regency. The UKM produces various types of footwear, including leather shoes, sports shoes, casual shoes, and sandals. In order to increase sales profits and avoid product buildup resulting from a decline in market demand. BSL Store needs to optimize the amount of production to maximize profits or minimize losses by using the Branch and Bound and Cutting Plane methods in solving linear integer programming problems. Based on the research, we get the same results for Branch and Bound method and the Cutting Plane method. BSL Store must produce 531 pairs of leather shoes, 744 pairs of sports shoes, 676 pairs of casual shoes, and 826 pairs of sandals get an optimum profit of Rp.62,080,000.00 it means that these two methods can be used by BSL Store in determining the amount of production BSL Store.